Praktik Penerapan Manajemen Sumber Daya Manusia Berbasis Islam pada Multazam Hotel - Fauzi, Amin; , Ahmad Madalis, SE., MBA (2017)
This study uses a qualitative method in which information were collected by interview and observation in more depth during a certain period so that they can dig and get more information about the application of HR manager practices based on Islamic values. The object of this research is engaged with the Islamic system Multazam Hotel. Then the sample in this study were employees of the hotel Multazam working as a HR manager and staff Acounting. The results stated that outlines the values of Islam have been applied, but not entirely. Aspects of Islam shown by entering the test criteria of reading the Qur'an in the selection and assessment of Al-Quran and Hadith in employee development activities. Recruitment of employees based on the needs of each department, but the priority in receiving the employee is a Muslim and has a good faith.